2017
DOI: 10.3390/nu9040346
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Induces Hepatic Steatosis Involving ER Stress Response in High Methionine Diet-Fed Mice

Abstract: Elevated circulating homocysteine (Hcy) has been proposed to be associated with non-alcoholic fatty liver disease (NAFLD). It is also reported that Hcy causes protein misfolding in the endoplasmic reticulum (ER). In this study, we used a high methionine diet (HMD)-fed mouse model and cultured primary hepatocytes to investigate the effects of Hcy on hepatic lipids metabolism. C57BL/6J mice received either standard chow diet (CT, n = 10) or diet supplemented with 2% methionine (MET, n = 10) for 16 weeks. In in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 31 publications
2
50
0
2
Order By: Relevance
“…Although ER stress can contribute to the development of steatohepatitis by increasing lipid synthesis and hepatocyte injury a physiological concentration of homocysteine showed distinct functions in hepatocytes. We assessed the effect of homocysteine at concentrations of 10 and 100 μM in in vitro experiments, which reflect healthy and hyperhomocystinuria‐inducible conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ER stress can contribute to the development of steatohepatitis by increasing lipid synthesis and hepatocyte injury a physiological concentration of homocysteine showed distinct functions in hepatocytes. We assessed the effect of homocysteine at concentrations of 10 and 100 μM in in vitro experiments, which reflect healthy and hyperhomocystinuria‐inducible conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Before we undertook our experiments, we initially expected that homocysteine supplementation would induce more severe steatohepatitis, as previous reports have shown that homocysteine induces lipid synthesis and cell injury through ER stress . However, homocysteine supplementation instead improved steatohepatitis by reducing the ER stress in mice on a choline‐deficient diet.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was demonstrated that excess SAM triggered the synthesis of triglycerides, ultimately leading to hepatic steatosis and the development of NAFLD [15]. Additionally, it was reported that elevated levels of Hcy induce hepatic steatosis by activating ER stress responses [16]. ER stress responses in turn can result in oxidative stress, inflammatory cell infiltration and fibrosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, reduction in intake of Met or Met restriction is reported to result in beneficial effects like increase in energy expenditure, longevity, improvement of insulin sensitivity and reduction in adiposity [26][27][28]. There are animal studies documenting toxic effects of diets supplemented with high levels of Met (2% and above) [14,16]. Importantly, Met has been reported to induce hypercholesterolemia (HChol) by enhancing Cho synthesis in the liver [29].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have suggested that Hcy-related endoplasmic reticulum stress increases the expression of sterol regulatory element-binding proteins (SREBPs), which further promote cholesterol and triglyceride synthesis [11]. The result was reproduced in an animal experiment by using methionine diet-fed mice, revealing elevated plasma triglyceride in increased plasma Hcy mice [12]. However, the relation between Hcy and triglyceride is not so consistent.…”
Section: Discussionmentioning
confidence: 99%